2004
DOI: 10.1590/s0100-29452004000100041
|View full text |Cite
|
Sign up to set email alerts
|

Pineapple yield and fruit quality effected by NPK fertilization in a tropical soil

Abstract: There is a lack of information about fertilization of pineapple grown in the State of São Paulo, Brazil. So a field experiment with pineapple 'Smooth Cayenne' was carried out to study the effects of NPK rates on yield and fruit quality. The trial was located on an Alfisol in the central part of the State of São Paulo (Agudos county). The experimental design was an incomplete NPK factorial, with 32 treatments set up in two blocks. The P was applied only at planting, at the rates of 0; 80; 160 and 320 kg/ha of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
1
70

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(139 citation statements)
references
References 4 publications
6
62
1
70
Order By: Relevance
“…Fertilizers were surface applied, close to the plant base, on an area of maximum root activity, according to the following application schedule: 10%, 30%, 30%, and 30% of the total rate, respectively 1, 5, 7, and 9 months after planting. These optimal N, P, and K rates and fertilizers splitting schedule were determined in recent trials conducted with pineapple in the same region by Spironello et al (2004) and Teixeira et al (2002).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fertilizers were surface applied, close to the plant base, on an area of maximum root activity, according to the following application schedule: 10%, 30%, 30%, and 30% of the total rate, respectively 1, 5, 7, and 9 months after planting. These optimal N, P, and K rates and fertilizers splitting schedule were determined in recent trials conducted with pineapple in the same region by Spironello et al (2004) and Teixeira et al (2002).…”
Section: Methodsmentioning
confidence: 99%
“…Potassium is the foremost nutrient required for pineapple crop and the lack of this nutrient reduces plant growth, fruit yield and affects negatively fruit quality as pointed out by Lacoeuilhe (1978 and Spironello et al (2004). Therefore, potassium fertilization plays an important role to pineapple yield, but high rates of potassium chloride, the most common and cheapest source of this nutrient, can negatively affect fruit size and some internal fruit characteristics, as compared with potassium sulphate (LACOEUILHE, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Estes aumentos também foram observados por Spironello et al, (2004) (2000). Deficiências de N e S reduzem a síntese de aminoácidos e, consequentemente, a de proteínas, promovendo maior disponibilidade de fotoassimilados para serem usados na síntese de compostos do metabolismo secundário, como, por exemplo, ácido ascórbico; ocorre, também, acumulação de outros ácidos orgânicos, principalmente os do ciclo dos ácidos tricarboxílicos (MARSCHNER, 1995).…”
Section: Teor De Sucounclassified
“…Alguns trabalhos sobre nutrição mineral e a qualidade dos frutos foram realizados com as cultivares Smooth Cayenne (SPIRONELLO et al, 2004;PAULA et al, 1999), Pérola (VELOSO et al, 2001), MD-2 (MARTINS et al,2008) e Queen Vitória (BHUGALOO et al, 1999) e na cv. Gandul (RAZZAQUE;RANAFI, 2001).…”
Section: Introductionunclassified
“…The hemiepiphytic cactus Hylocerus undatus presented 25 g N/kg in joints (Nobel & Barrera, 2004) , the long-distance transport within the plant between K + and NO 3 -, and absorption and partitioning of K in plant which can be altered by the form of applied N (Bar Tal, 2011), as the authors also observed in Mulder interaction diagram, modified by Malavolta (1980); however, the authors did not observe an increase of Mg contents, as a trend indicated in the diagram. The decrease of concentration of K and P in pineapple was due to a dilution effect promoted by high concentration of urea which triggered a rapid and vigorous vegetative growth, which also seem to be occurring in epiphytic cacti (Spironello et al, 2004). The highest P content in joints was 7.7 g/kg at dose of 33.3 mM N in Rhipsalis baccifera, whereas for R. paradoxa and H. salicornioides the contents decreased with an increase of urea in HA solution.…”
Section: Resultsmentioning
confidence: 94%